Relationship between the price of raw materials of fabric with the amount of production produced - Ryan Riwanto Dwitomo; Shadiya Nada Syahrani; Calvin Zovian; Imam Sybro M; Glenn Darmadi; Tiara Diva Lidya Asliyah; M Diva Rifandi Andana; Muhammad Ardiansyah (Privietlab, 2021)
Production is an activity carried out by a company to add use to an object or create new objects that are more useful for everyone to meet their needs. The Covid-19 pandemic has had a major impact on the textile sector. During this pandemic, demand in the local market has decreased significantly. The stock of goods owned by the local market cannot accommodate the decrease in demand. For convection or garment companies, the price of raw materials has increased by up to 30%. This increase certainly has an impact that makes it difficult to get raw materials for the production process. These results indicate that when the price of raw materials increases, there will be an increase in production, but when the price of raw materials decreases, it will make production decreases. An increase in production when the price of raw materials increases is a sign that garment business actors are still trying to meet consumer needs for garment products. This also indicates that garment entrepreneurs continue to increase production when raw material prices increase, which indirectly indicates that the garment industry has good potential to survive the COVID-19 pandemic.